Sucrose Hydrolysis and Phenolics Production by Daucus Carota Entrapped in Hollow Fiber Reactors - Jose, Wilfredo I.; Pedersen, Henrik; Chin, Chee Kok (Philippine Engineering Journal; Vol 31 No 2 (2010), 2021)
No Abstract. Foreword by Dr. Rizalinda L. De Leon.